2023
DOI: 10.1093/europace/euad058
|View full text |Cite
|
Sign up to set email alerts
|

Time of onset of atrial fibrillation and atrial fibrillation progression data from the RACE V study

Abstract: AimsAtrial fibrillation (AF) progression is associated with adverse outcome, but the role of the circadian or diurnal pattern of AF onset remains unclear. We aim to assess the association between the time of onset of AF episodes with the clinical phenotype and AF progression in patients with self-terminating AF.Methods and resultsThe Reappraisal of AF: Interaction Between Hypercoagulability, Electrical Remodelling, and Vascular Destabilization in the Progression of AF study included patients with self-terminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Results from the RACE V trial demonstrated that patients with a predominant pattern of AF occurrence (daytime or nocturnal) have a better comorbidity profile compared with those with a mixed pattern of AF. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Results from the RACE V trial demonstrated that patients with a predominant pattern of AF occurrence (daytime or nocturnal) have a better comorbidity profile compared with those with a mixed pattern of AF. 16 …”
Section: Discussionmentioning
confidence: 99%
“…This subanalysis includes 417 patients, all having a follow-up duration of ≥1 year. 20 No patients were lost to follow-up in this first year or died before AF progression. Patients or the public were not involved in the design, or conduct, or reporting or dissemination plans of our research.…”
Section: Methodsmentioning
confidence: 99%
“…As described previously, AF progression was defined as (1) the development of persistent or permanent AF during follow-up or (2) an increase of >3% AF burden over the first 6 months or total follow-up. 18 The 3% cutoff has been published previously, and details concerning the 3% cut-off for AF burden can be found in the paper by Nguyen et al [19][20][21] The duration of monitoring for the current analysis lasted until 1 May 2020, until the last available rhythm monitoring for patients who died after >1 year of continuous rhythm monitoring or until the date of PVI in case of a successful PVI.…”
Section: Af Progressionmentioning
confidence: 99%
“…Recent data from the RACE V registry suggest that paroxysmal AF has a higher burden that can be further differentiated into subgroups. 76 , 77 While continuous rhythm monitoring is the preferred method to evaluate AF burden, serial longer-term monitor 10 , 78 or even long-term intermittent monitoring by recording one to three short-term handheld ECGs per day provides effective, albeit less precise alternative methods. 79 So far, these rhythm monitoring methods have mainly been used in research settings.…”
Section: Atrial Fibrillation Burden In Patients With Electrocardiogra...mentioning
confidence: 99%